Ranking historic: UUM - Daily Express, (KK) (Daily Express, 2017)
AlOR SETAR: Universiti Utara Malaysia(UUM) has been listed in the top 200+ placing in the first edition of the Times Higher Education AsiaPacific University Rankings (THE APAC) 2017 which was announced recently.